Hubungan pengetahuan remaja putri tentang kanker payudara dengan tindakan SADARI - Syahda Sayidah Fatimah; Papat Patimah; Shinta Arini Ayu (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Introduction: Breast cancer is one of the most common types of cancer among women and can be detected early through breast self-examination (BSE). However, the practice of breast self-examination among adolescent girls remains low due to a lack of knowledge regarding breast cancer and early detection. Purpose: To determine the relationship between adolescent girls' knowledge of breast cancer and the practice of breast self-examination. Method: This study employed a quantitative research design using a correlational approach and a cross-sectional study design. The sample consisted of 97 respondents selected through purposive sampling at State Vocational High School 2 Cilaku, Cianjur Regency. Data were collected using a questionnaire covering knowledge of breast cancer and breast self-examination (BSE) practices, and were subsequently analyzed using the Chi-Square test. Results: The majority of respondents were 17 years old (46.4%) and in the 11th grade (n=59; 60.8%). Most respondents possessed a moderate level of knowledge (n=68; 70.1%), yet the majority did not practice breast self-examination. Chi-Square test results indicated a significant relationship between adolescent girls' knowledge of breast cancer and the practice of breast self-examination (p < 0.05). Conclusion: Adolescent girls' knowledge is significantly associated with the practice of breast self-examination. Continuous health education regarding breast cancer and early detection through breast self-examination should be implemented in schools to raise awareness and encourage better early detection practices among adolescent girls. Keywords: Adolescent Girls; Breast Cancer; Breast Self-Examination; Knowledge.